La consulta previa en materia ambiental en la reserva ecológica arenillas (R.E.A) Arenillas provincia de El Oro 2014. - Tinoco Sánchez, Jhon Roberto (2015)
Some municipal governments have taken the initiative of go by structuring its own protected areas, especially to ensure their populations sources of water in a sustainable way. The Municipal Government of grit has had an important role in this regard. Since the year 2000 he began to declare public a series of sites and areas located in the forest park of grit for conservation in the long term. This thesis aims to reveal to the community, the environmental policy that the Government is running to protect the ecosystems of the canton, for which we develop a research work focused on the consultation for the conservation of the Arenillas ecological reserve (REA). Sustain us in the standard-setting process, and other other declarations that make up an appropriate legal framework that guarantee this work coordinated with the Arenillense community and the different sectional levels. We demonstrate that there is interest and the need to address the issue with greater dynamism and identifying characteristics sufficient to propose a binding consultation in the municipality of grit in the lathe to the protection and conservation of this protected ecosystem. From the side of private organizations, conservation initiatives not have been able to integrate provincial or State process for lack of a legal regulation of support. The most consistent effort in terms of getting citizenship occurs we raised a proposal firmly consolidate the binding query to boost the protection of this ecological reserve of Orense. We developed this theme of academic work to report that the Government has developed a series of policies that are aimed at the exploitation of nonrenewable natural resources in territories inhabited by communities, peoples and nationalities, which has generated a reaction of the inhabitants of the community, special Arenillense, Orense, and even of the Ecuadorian coast, since by the advance of the desert of the neighboring country of the South airdue to the distribution of the reservation to groups or landless farmers alleged, would do it is through the Ecuadorian Government and does not you have fulfilled in the proper regulation with the provisions of the Constitution and the law on environmental management in relation to the consultation, so in this case did not do so is binding form to the community, Arenillense or Orense, which has led to a possible infringement of the rights of these peoples concerning their habitat to be able to the Sumak Kawsay.